The intriguing dose-dependent effect of selected amphiphilic compounds on insulin amyloid aggregation: Focus on a cholesterol-based detergent, Chobimalt - Siposova, Katarina; Petrenko, Viktor I.; Garcarova, Ivana; Sedlakova, Dagmar; Almásy, László; Kyzyma, Olena A.; Kriechbaum, Manfred; Musatov, Andrey (Frontiers in Molecular Biosciences, 2022)
The amyloidogenic self-assembly of many peptides and proteins largely depends on external conditions. Among amyloid-prone proteins, insulin attracts attention because of its physiological and therapeutic importance. In the present work, the amyloid aggregation of insulin is studied in the presence of cholesterol-based detergent, Chobimalt. The strategy to elucidate the Chobimalt-induced effect on insulin fibrillogenesis is based on performing the concentration- and time-dependent analysis using a combination of different experimental techniques, such as ThT fluorescence assay, CD, AFM, SANS, and SAXS. While at the lowest Chobimalt concentration (0.1 µM; insulin to Chobimalt molar ratio of 1:0.004) the formation of insulin fibrils was not affected, the gradual increase of Chobimalt concentration (up to 100 µM; molar ratio of 1:4) led to a significant increase in ThT fluorescence, and the maximal ThT fluorescence was 3-4-fold higher than the control insulin fibril´s ThT fluorescence intensity. Kinetic studies confirm the dose-dependent experimental results. Depending on the concentration of Chobimalt, either (i) no effect is observed, or (ii) significantly, ~10-times prolonged lag-phases accompanied by the substantial, ~ 3-fold higher relative ThT fluorescence intensities at the steady-state phase are recorded. In addition, at certain concentrations of Chobimalt, changes in the elongation-phase are noticed. An increase in the Chobimalt concentrations also triggers the formation of insulin fibrils with sharply altered morphological appearance. The fibrils appear to be more flexible and wavy-like with a tendency to form circles. SANS and SAXS data also revealed the morphology changes of amyloid fibrils in the presence of Chobimalt. Amyloid aggregation requires the formation of unfolded intermediates, which subsequently generate amyloidogenic nuclei. We hypothesize that the different morphology of the formed insulin fibrils is the result of the gradual binding of Chobimalt to different binding sites on unfolded insulin. A similar explanation and the existence of such binding sites with different binding energies was shown previously for the nonionic detergent. Thus, the data also emphasize the importance of a protein partially-unfolded state which undergoes the process of fibrils formation; i.e. certain experimental conditions or the presence of additives may dramatically change not only kinetics but also the morphology of fibrillar aggregates.